An approach to estimate CCV (cycle-to-cycle variation) of effective energy output of thermal engine: A case study on a high speed gasoline engine. (December 2021) - Chen, Yangyang; Deng, Banglin; Chen, Mingmin; Hou, Kaihong
Abstract: Cycle-to-cycle variations (CCV) of engine (or other power sources) effective power output is a crucial parameter for engine itself and connecting machines, but limited by the response characteristic of measuring instrument, it is still an unattainable parameter. In the current study, an approach is proposed to estimate the cyclic variations of engine effective power output. We designed two experiment scenarios to measure in-cylinder parameters in cyclic level and engine friction loss. Then, friction loss modeling is calibrated by this experimental data, such that in-cylinder parameters (especially maximal pressure) and engine operating parameters (such as speed) can be integrated into FMEP in cyclic level. Thus, cyclic variation of effective power output can be finally deduced. We found that Chen-Flynn friction loss model can well predict FMEP after careful calibration. The FMEP keeps synchronously with Pmax against cycle and FMEP generally decreases cycle fluctuation of BMEP, the average COV of BMEP is lower than that of IMEP by ∼33% and ∼32% at 60% and 100% load, respectively. CCV of BMEP shows nonsynchronous characteristics relative to that of IMEP, this is affected by cycle evolution feature of FMEP. So, CCV of in-cylinder parameters cannot be directly used to assess CCV of effective power output. Finally, when the CCV output is considered in analysis of connecting machines, the transmission accuracy for connecting machines is deteriorated largely, and the vibration and sound will be more intense. Thus, the engine CCV output cannot be ignored in assessment of connecting machines.